2018
DOI: 10.5334/joc.9
|View full text |Cite
|
Sign up to set email alerts
|

Can Intrinsic and Extrinsic Metacognitive Cues Shield Against Distraction in Problem Solving?

Abstract: We investigated the capacity for two different forms of metacognitive cue to shield against auditory distraction in problem solving with Compound Remote Associates Tasks (CRATs). Experiment 1 demonstrated that an intrinsic metacognitive cue in the form of processing disfluency (manipulated using an easy-to-read vs. difficult-to-read font) could increase focal task engagement so as to mitigate the detrimental impact of distraction on solution rates for CRATs. Experiment 2 showed that an extrinsic metacognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
(113 reference statements)
3
17
1
Order By: Relevance
“…In the current study, task-engagement was increased by making the text disfluent, thereby rendering it more difficult to read. However, it is likely that other manipulations of task-engagement such as incentive for good task performance can have similar distraction-shielding effects (Ball et al, 2018;Seli et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, task-engagement was increased by making the text disfluent, thereby rendering it more difficult to read. However, it is likely that other manipulations of task-engagement such as incentive for good task performance can have similar distraction-shielding effects (Ball et al, 2018;Seli et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, if the halfalogue is only more disruptive than the dialogue for the normal speech condition, then the semantic (un)predictability account would prevail (Emberson et al, 2010;Monk, Fellas, & Ley, 2004;Norman & Bennett, 2014 font shields against distraction in paradigms that are theoretically-oriented (Hughes et al, 2013;Marsh, Sörqvist, & Hughes, 2015), and for tasks that hold applied relevance for office and scholastic environments such as proofreading and reading comprehension (Faber, Mills, Kopp, & D'mello, 2017;Halin, 2016;Halin, Marsh, Haga et al, 2014;Halin, Marsh, Hellman et al, 2014). A typical explanation of these findings is that the perceptually disfluent font acts as a metacognitive cue that the task is difficult (e.g., Bjork, Dunlosky, & Kornell, 2013;Thompson, 2010), with the metacognitive system instigating a compensatory upward shift in task-engagement (or concentration) such that an individual can maintain a desired performance level Eggemeir, Crabtree, & LaPointe, 1983; see also Ball, Threadgold, Solowiej, & Marsh, 2018). It is suggested that the greater task-engagement that the perceptually disfluent font demands, leads to a more steadfast locus of attention (e.g., unexpected irrelevant stimuli are less likely to capture attention away from the focal task) and reduces processing (and therefore awareness) of the surrounding environment .…”
Section: Aims Of the Current Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our reasoning was to keep participants engaged in this difficult task, the added motivation may have impacted our results. For example, Ball, Threadgold, Solowiej, and Marsh (2018) demonstrated that motivation can impact the degree to which background speech impairs verbally-based problem solving and it is possible, therefore, that inducing motivation may have diminished the effectiveness of the task-difficulty manipulation in modulating distraction through top-down control (cf. Ball et al, 2018; Hughes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, limiting opportunities for subvocalisation by presenting task-irrelevant sounds also hampers concurrent CRAT performance (Ball et al, 2018;Threadgold et al, 2019). For example, Threadgold et al (2019) demonstrated that meaningless irrelevant sound (Spanish vocal music presented to monolingual English-speaking participants; Experiment 1) or non-vocal, instrumental music (Experiment 2) impaired solution accuracy for CRAT problems relative to quiet.…”
Section: Retrieval and Rehearsal Processes As Determinants Of Crat Anmentioning
confidence: 99%